The twelve days of Christmas - Jeffers, Susan (Harper, an imprint of HarperCollinsPublishers, 2013)
On Christmas Eve, Emma discovers a magical music box with a classic holiday tune that unites her with Santa Claus, and together they travel to the North Pole.